ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI EXPLORE BROMO TOUR & TRAVEL - I Putu Sudhyana Mecha; Randhi Nanang Darmawan; Rosilia Putri Tania (Jurnal Pijar, 2023)
Explore Bromo Tour & Travel is a company engaged in the field of travel agency services, is required to prioritize the quality of service to customers or tourists. The purpose of this study was to determine and analyze the effect of service quality on customer satisfaction partially on Explore Bromo Tour and Travel. The approach chosen in this research is a quantitative approach with the type of correlation research. The population in this study are customers who use Explore Bromo Tour and Travel services, from April to October 2021. The sample in this study uses the Probability Sampling technique, the type of method is Simple Random Sampling totaling 52 customers who use Explore Bromo Tour and Travel services. from April to October 2022. Data collection techniques used interviews and questionnaires. The results of the study can be concluded that the calculation of t arithmetic is bigger than t table, with the result of 7.543 which shows a partially significant influence between service quality consisting of Tangible, Reliability, Responsiveness, Assurance and Empathy on customer satisfaction Explore Bromo Tour and Travel Malang. Reliability factor is the most influential factor on customer satisfaction Explore Bromo Tour and Travel Malang